Intelligent operations of the data acquisition system of the ATLAS experiment at LHC. (April 2015) - Anders, G; Avolio, G; Miotto, G Lehmann; Magnoni, L
Abstract: The ATLAS experiment at the Large Hadron Collider at CERN relies on a complex and highly distributed Trigger and Data Acquisition (TDAQ) system to gather and select particle collision data obtained at unprecedented energy and rates. The Run Control (RC) system is the component steering the data acquisition by starting and stopping processes and by carrying all data-taking elements through well-defined states in a coherent way. Taking into account all the lessons learnt during LHC's Run 1, the RC has been completely re-designed and re-implemented during the LHC Long Shutdown 1 (LS1) phase. As a result of the new design, the RC is assisted by the Central Hint and Information Processor (CHIP) service that can be truly considered its "brain". CHIP is an intelligent system able to supervise the ATLAS data taking, take operational decisions and handle abnormal conditions. In this paper, the design, implementation and performances of the RC/CHIP system will be described. A particular emphasis will be put on the way the RC and CHIP cooperate and on the huge benefits brought by the Complex Event Processing engine. Additionally, some error recovery scenarios will be analysed for which the intervention of human experts is now rendered unnecessary.